Multi‐species, multi‐country analysis reveals North Americans are willing to pay for transborder migratory species conservation. Issue 2 (21st February 2022) - Thogmartin, Wayne E.; Haefele, Michelle A.; Diffendorfer, Jay E.; Semmens, Darius J.; Derbridge, Jonathan J.; Lien, Aaron; Huang, Ta‐Ken; López‐Hoffman, Laura
Abstract: Migratory species often provide ecosystem service benefits to people in one country while receiving habitat support in other countries. The multinational cooperation that could help ensure continued provisioning of these benefits by migration may be informed by understanding the economic values people in different countries place on the benefits they derive from migratory wildlife. We conducted contingent valuation surveys to estimate the willingness of 3733 respondents from Canada, the United States and México to invest in conservation for two disparate migratory species, the northern pintail duck Anas acuta and the Mexican free‐tailed bat Tadarida brasiliensis mexicana . With zero‐inflated mixed‐effects negative binomial regression (explaining 87% of the variation in willingness to pay for conservation), we found that respondents from each nation, after controlling for both household income and per capita national Gross Domestic Product, were willing to invest in conservation in other countries. This willingness to pay for conservation, even when respondents knew that funds would be used to support benefits accruing primarily in other countries, demonstrates the potential for support of multinational conservation policies and programmes that direct resources to locations where the most critical habitat is located, rather than where the funding is generated. These findings could be used to support the development or expansion of new and existing international conservation programmes for migratory species. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resumen: Con frecuencia las especies migratorias brindan beneficios de servicios ecosistémicos a la gente en un país mientras reciben soporte de su hábitat en otros países. La cooperación multinacional requerida para asegurar el suministro continuo de los beneficios de procesos migratorios puede justificarse con el entendimiento de los valores económicos que la gente de diferentes países da a los beneficios provenientes de especies migratorias. Llevamos a cabo encuestas de preferencias públicas para estimar la disposición de encuestados de Canadá, Estados Unidos y México para invertir en la conservación de dos especies migratorias, el pato golondrino Anas acuta y el murciélago de cola libre mexicano Tadarida brasiliensis mexicana . Con una regresión binomial negativa de estimación del modelo de efectos mixtos inflados a cero (el cual explica el 87% de la variación en la disposición para pagar por la conservación), encontramos que los encuestados de cada país, después de controlar tanto el ingreso familiar como el Producto Interno Bruto nacional per cápita, estaban dispuestos a invertir en la conservación en otros países. Esta disposición para pagar por la conservación, incluso respaldar los beneficios acumulados a través de fronteras internacionales, permite potencialmente la asignación de recursos multinacionales hacia aquellos lugares donde las especies se benefician más y, como resultado, la continua transferencia de beneficios de servicios ecosistémicos a través de la migración de especies.